Analysis of the Main Controlling Factors of Oil and Gas Accumulation in the South China Sea Using Ya’nan Sag as an Example - Chengquan Shi; Fei Yang; Yin Xu; Rui Fan; Zihao Ye (Energies)
The Ya’nan sag has experienced more than 40 years of exploration, but only the Ya 13-1 large gas field has been found. In recent years, no oil or gas field has been found, and exploration work is difficult. To clarify the main controlling factors of the oil and gas reservoirs in Ya’nan Sag, the direction of oil and gas exploration is highlighted. Based on 3D seismic data combined with drilling information, this paper determines the basic geological conditions, clarifies the main controlling factors of reservoir formation, and predicts strong exploration directions. The research revealed the following: ① The source rocks of the Yacheng Formation in the Ya’nan sag are developed, and the types are II2-III, with excellent resource potential. ② In-depth analysis of the drilled wells revealed that high-quality reservoirs, oil-source faults, and caprock conditions are the main controlling factors of hydrocarbon accumulation in Ya’nan sag.